(untitled) (Al-Qamar, 2022)
The Book’’ Sharh Maʻānī al-Āthār by Imam al-Tahāvī Abu Jafer Ahmad bin Muhammad al-Tahāvī has high rank among the Hadith books. It’s one of the most authorized book of ’’Hanfi School of Thought’’. Its method is scientific and its way of arguments is rational. It presents the corpus of Hanfi School of thought in its proved and preferred form and makes an organic link with the other school of thought. The basic reason for its popularity is the reliability of its statement Nazer . This article aims to throw light on introduction of the book in concise and precise manner as well as the scholarly contribution of the author has been discussed in detail. After understanding of this book, readers will be able to have grip on the way of argument of jurists and their method of ’’ Nazer’’